Hierarchical isometry properties of hierarchical measurements - Flinth, Axel; Gross, Benedikt; Roth, Ingo; Eisert, Jens; Wunder, Gerhard (Applied and Computational Harmonic Analysis, 2022)
Compressed sensing studies linear recovery problems under structure assumptions. We introduce a new class of measurement operators, coined hierarchical measurement operators, and prove results guaranteeing the efficient, stable and robust recovery of hierarchically structured signals from such measurements. We derive bounds on their hierarchical restricted isometry properties based on the restricted isometry constants of their constituent matrices, generalizing and extending prior work on Kronecker-product measurements. As an exemplary application, we apply the theory to two communication scenarios. The fast and scalable HiHTP algorithm is shown to be suitable for solving these types of problems and its performance is evaluated numerically in terms of sparse signal recovery and block detection capability.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Block detection; Hierarchical sparsity; Internet of Things; MiMO; Structured compressed sensing; Thresholding algorithms